Deteksi 4 Tanda Vital Pasien Rumah Sakit Berbasis Fuzzy Database - Rangkuti, A Haris (Bina Nusantara University, 2013)
To assist the performance of medical technicians in nursing patients effectively and efficiently, information technology appears as a dominant support. Utilizing information technology, patient?s diagnoses can be reported to a doctor as soon as possible, as well as the patient's condition which needs to be monitored regularly. It is necessary to build a monitoring information system of hospital that is able to present timely information regarding the patient's condition characterized by four vital signs which are temperature, blood pressure, pulse, and respiration. For the four vital signs monitoring, fuzzy logic concept is implemented. If vital signs approach 1, the patient is close to recovery. Conversely, if the signs are 0, the patient still needs medical treatment. This system also helps nurses in order to provide answers to the families of patients who want to know the development of the patient's condition, as well as the recovery based on the average percentage of Fuzzy max of four vital signs. By Fuzzy-based monitoring system, monitoring the patient's condition becomes simpler and easier.